Methods for determining the biocompatibility of dental materials - Ríos, Valentina; Romero, Natali; Valencia, Carlos; Balanta, Julián (Revista Estomatología, 2014)
Background: The dental materials are subjected to various tests for consistency, bioactivity, and demonstrate that they can remain in the oral environment without producing an adverse response. Currently for this purpose worldwide are employed different techniques such as cell culture, techniques of molecular biology and the use of shrimp larvae (brineshrimplarvae) better known as Artemia salina. Objective: Characterize five dental materials using a cytotoxicity test with larval shrimp Artemia salina. Materials and methods: A cytotoxicity study was performed on samples of Titanium Type IV, Silicone Heavy, Auto-cured acrylic resin and photo-curing and Eugenolatousing the method of Artemia salina. Results: The cytotoxicity assay for Artemia Salina showed no viability foreugenolato because all the larvaes were eliminated, and other products showed biocompatibility in the following percentages. Titanium type IV 100%, the silicone 46%, acrylic 62% and resin 72%. Conclusions: The method of brine shrimp is a simple and economical method for studies of cytotoxicity, requires greater infrastructure technology, and combined with other techniques of cell biology can become as specific method as desired. There is viability for the artemiasalina larvae with type IV titanium of 100% and with eugenolato of 0%.